Study on crashworthiness of nature-inspired functionally graded lattice metamaterials for bridge pier protection against ship collision. (15th February 2023) - Nian, Yuze; Wan, Shui; Wang, Xiao; Zhou, Peng; Avcar, Mehmet; Li, Mo
Highlights: A new nature-inspired functionally graded lattice metamaterial filled protection structure is designed and investigated. The graded metamaterial filler shows great potential to improve the crashworthiness of thin-walled structures. The graded model has a major influence on the crashworthiness of the novel composite structures. Parametric analysis is adopted to study the energy absorption characteristics of vessel-protection-bridge pier collision. Abstract: Lightweight lattice metamaterials can effectively enhance the impact resistance of thin-walled structures. With the aim of further investigating the potential of lattice-filled composite structures, an innovative nature-inspired functionally graded lattice filled protection structure (FGLPS) is proposed in this paper to enhance structural energy absorption characteristics under ship impact loadings. At this point, two different graded patterns (i.e. increasing graded pattern and decreasing graded pattern with partition design) for lattice metamaterial fillers are established, then the effects of gradient model and impact angle on energy absorption characteristics of lattice-filled structures are studied using ship impact finite element model with multiple collision conditions. The results show that the novel functionally graded lattice filled thin-walled structure can significantly reduce the peck impact force, prolong the impact time and play prominent protective role. Especially, the peak impact force generated during the vessel impact on bridge pier can be reduced by up to 60.01% through zonal gradient design. Besides, FGPLS can absorb up to 33.15% of total impact energy by plastic deformation, and both increasing and decreasing gradient structure have the potential ability to significantly reduce the impact damage. The findings of this study provide a new approach to the engineering applications of collision-resistant structures with high energy absorption capacity.